Doktrin Ekonomi Kesejahteraan Ternyata Lebih Dekat Ke Ajaran Islam - Supardi, Author: (Unisia, 2010)
In Indonesia, social welfare denotes Imperative-Ideology, and it also constitutes constitutional demand. If modem economics tends to separate efficiency from ethics that judge wrong or right teaching, or fair or unfair doctrine, ethical economics force to unity both. Social welfareIs the general continuity of welfare economics that contains ethical norms/values. In this respect Islamic economics building is universally, that means that this system actualize all human. Similar to Islamic economics, welfare economics as a economical system that will be applied In Indonesia Including all Indonesian citizen, and economists have equal some opportunities to reach the goal of economy.